Variation in Practice Patterns for Listing Patients for Renal Transplantation in the United Kingdom: A National Survey. Issue 6 (June 2018) - Pruthi, Rishi; Tonkin-Crine, Sarah; Calestani, Melania; Leydon, Geraldine; Eyles, Caroline; Oniscu, Gabriel C.; Tomson, Charles; Bradley, Andrew; Forsythe, John L.; Bradley, Clare; Cairns, John; Dudley, Christopher; et al.
Abstract : Background: Despite the availability of guidelines for the evaluation of candidates for renal transplantation, variation in access to transplantation exists. This national survey investigates whether center variation exists in the assessment of patients for renal transplantation in the United Kingdom. Methods: An online survey, informed by qualitative interviews, was distributed to all UK renal centers. This survey examined center approaches to chronic kidney disease service provision, transplant recipient assessment, education provision, and waitlisting decision making processes. Center reevaluation policies for patients already listed and priorities for future development were also examined. Results: All 71 renal centers responded. Of these, 83% reviewed predialysis patients in a low clearance clinic. In 26% of the centers, transplantation was not discussed as a treatment option with all patients. Fourteen centers reported having a dedicated transplant assessment clinic, whereas 28% did not have a formal assessment protocol. Age was an exclusion criterion for listing in 3 centers, all of which had a cutoff at 75 years. Eighty-three percent of the centers excluded patients with a high body mass index. Cardiac investigations were risk-stratified in 90% of centers. Surgical involvement varied with 11% of centers listing patients without formal surgical review. There was no formal protocol in place to reevaluate listed patients in 62% of centers. Conclusions: There is wide variation in UK practice patterns for listing patients for renal transplantation, though its impact on access to transplantation is unclear. The extent to which center-specific and patient-specific factors affect access to transplantation requires further analysis in a prospective cohort of patients. Abstract : There is wide variation, including center-specific and patient-specific factors in UK practice patterns for listing patients for renal transplantation and its impact on access to transplantation should be analyzed in a prospective cohort of patients.